Analisis Ketidaksesuaian Data Stock Opname Material pada Gudang Material di PT UPX - Amiatul Wafa; Agung Syukriadinata (Study Program of Industrial Engineering, Udayana University, 2025)
Inventory management is an important component in the smooth operation of a company, especially in the energy generation sector. PKT is experiencing discrepancies between system data and physical stock opname results. These discrepancies disrupt stock control performance and can cause operational disturbances. The objective of this research is to identify the main factors contributing to data discrepancies and provide improvement recommendations using the Six Sigma approach combined with the DMAIC method (Define, Measure, Analyze, Improve, Control). This methodology is used to identify problems, measure the level of deviation, analyze root causes, create improvement solutions, and monitor the results of the improvements. The research results show that weaknesses in monitoring incoming and outgoing goods, as well as the lack of standardization in recording procedures, are the causes of data discrepancies. Recommendations for improvement include providing instructions to warehouse employees and optimizing the digital recording system.